Profit Maximization in Islam - Ghori, Sonia (International Journal of Islamic Banking and Finance Research, 2020)
The Islamic financial system is based on the betterment of society. It discourages any discrimination among the people and promotes equal distribution of wealth among the people. This study aims to investigate the concept of Profit maximization in Islam by taking evidence from the Quran, authentic Hadith, and Islamic scholars Fatwa. The center discussion of this paper would be based on theoretical aspects. Islam promotes the idea of business and trade, business profits, and motivates them to search and strive for ‘halal’ profit. This can be proved by different Quranic Verses and Hadith and Fatwa. The study also has a great example of our Holy Prophet (P.B.U.H). The convention of many hadith with the profit as a benchmark may be used as an alternative to interest in Islamic financing. The study is an effort to discuss the features of the Islamic concept of profitability and distinguish between halal and haram profit and discussed the questions to which extent profit is acceptable for Muslims.